Optimalisasi Waktu Tunggu Lampu Lalu Lintas menggunakan Simulasi Monte Carlo di Simpang Lima Ampenan Kota Mataram - Hardika Budianto; Amrullah Amrullah; Wahidaturrahmi Wahidaturrahmi; Arjudin Arjudin (Griya Journal of Mathematics Education and Application, 2022)
Transportation is basic human need in supporting various aspects of life, even almost all human activities require transportation. Arrangement of good traffic light are very needed at every intersection of the road. One of the very strategic intersection in Mataram city is Ampenan intersection. One of the factors that affect the accumulation of vehicle queues is less than optimal time when the green light is on at the traffic light. Therefore, it is necessary to study the optimal time of traffic lights based on amount of vehicles that passing and time of the green light is on. One of method to determine the optimal time of traffic light using Monte Carlo simulation method. Monte Carlo method is an algorithm for solving a problem to get better results using the probability distribution. Study uses the distribution of arrival and passing vehicles. Observation the time of arrival and passing vehicles is done in each direction of the traffic light. Results of this study indicate that the optimum time for the green light for the west direction are 21 seconds, for the east direction 21 seconds, for the north direction 36 seconds, and for the south direction 36 seconds.